A STUDY OF POST-PANDEMIC SUSTAINABILITY OF AGRO-TOURISM INDUSTRY IN VIDARBHA REGION (International Journal of Food and Nutritional Sciences, 2022)
Agro-tourism is basically a agricultural activity which attracts customers or visitors to farm or ranch and has different definitions across the world. Agro-tourism came into operation first by Pandurang Taware named as Baramati Agro tourism centre in Pune district. He also received National tourism award for his achievement. After that it spread by Agro-tourism Development Corporation has started Agro-tourism centers in Maharashtra with affiliated with more than 200 farmers. After that agro tourism business spread in other states of India like Punjab, MP, Tamil Nadu, Goa, Karnataka, West Bengal, kerala, Rajasthan, Uttarakhand, etc. Agro tourism is a new concept which relates to farming activities also provide best opportunity to know rural life farming and knowledge of local traditions. 95 million farmers are living in 7 lakhs villages which contributing Indian agriculture contributes 30% GDP. Agro-tourism has spread widely in metro cities like Pune, Mumbai, Sangali, Satara, Kolhapur, etc. Firstly Agro-tourism is started in Pune’s Baramati district by National tourism award winner from the president of India Mr. Pandurang Taware who receives the award for most Innovative tourism product. But what about the other regions of Maharashtra other than Metro cities? In Vidarbha region Agro- tourism is not known to many people as Vidarbha consists of 85% of Farmers and their main source of income is farming only. Very few Agro-tourism centers are there in Vidarbha and many of them are already closed due to lack of tourists. Research paper mainly focus on sustainability of Agro-tourism in Vidarbha region. Entrepreneurs who think of starting Agro-tourism in Vidarbha region will get great help from the paper.